Investigation of 2H/1T/1T′ phase MoS2 optical nonlinearity - Hsuan-Sen Wang; Shih-Po Su; Yi-Hsuan Huang; Li-Wei Tu; Paritosh V. Wadekar; Hsiang-Chen Wang; Chao-Kuei Lee (Discover Nano)
Abstract 2H and 1T/1T′ molybdenum disulfide (MoS2) are typical phases that can be found in crystalline and thin film materials. In this work, by controlling the atmosphere during thin film chemical vapor deposition, 2H or 1T/1T′ phase MoS2 are grown separately. Additionally, by employing the Z-scan technique, the phase-dependent optical nonlinearity of MoS2 is observed and investigated. The 2H phase-dominated few-layered MoS2 shows clear reversed saturable absorption with a peak intensity reaching $$3.3 \, \text{GW}/{\text{cm}}^{2}$$ 3.78 GW/cm2, indicating extra higher-order nonlinear absorption. In contrast with the 2H phase, dominant single photon absorption is observed in the 1T/1T′ phase MoS2. In addition, the nonlinear refractive index (n2) of the two phases is characterized, exhibiting values of 1.82 × 10–10 cm2/W (1T/1T′ phase) and − 4.82 × 10–10 cm2/W (2H phase). This is the first time that the phase-dependent optical nonlinearity of MoS2 has been distinguished. Meanwhile, the proposed methodology not only provides information on the differences between the phases but also serves as a guide for determining suitable phases in specific applications.